Medication Adherence to Successful Tuberculosis Treatment Outcome among TB/HIV Patient at Prof. Dr. Sulianti Saroso Infectious Disease Hospital - Yusmaniar Yusmaniar; Adin H Kurniawan (Universitas Padjadjaran, Indonesia, 2020)
Tuberculosis/Human Immunodeficiency Virus (TB/HIV) co-infection has poorer treatment outcome compared to non-co-infected patients. To benefit from therapy and to avoid contracting treatment-resistant strains, the individuals must adherent to medications. There is limited information regarding successful TB treatment outcomes and their associated factors. Thus, the study was designed to identify medication adherence associated with treatment outcomes among TB/HIV Patients at Prof. Dr. Sulianti Saroso Infectious Disease Hospital. This research was an observational study with retrospective approach from January 2015 to December 2017 by taking data from medical records and TB-01 form of TB/HIV patients in the outpatient clinic of the disease which would be used as a sample. Regarding compliance in treatment with first visit for 2-4 months, an approach using secondary data which were TB-01 Form, as well as HIV Care and Antiretroviral Therapy summary forms was used. The statistical analysis used was the bivariate analysis with the chi-square test as the statistical test. A total of 114 patients were included in the study. The outcome of treatment success obtained from this study had a patient cure rate of 91.30%. There is a significant relationship between medication adherence to successful tuberculosis treatment outcome with p-value= 0.012; OR= 5.684. There is a meaningful relation between medication compliance with treatment outcome. It is when on medication adherence, the treatment results can be declared cured in accordance with predetermined criteria, while when not on medication adherence, the treatment results are not declared cured.